Fixed versus flexible gonadotropin releasing hormone antagonist protocol in women with polycystic ovary syndrome undergoing in vitro fertilization: An RCT - Hanieh Fatehi; Robab Davar; Elham Nikfarjam; Fatemeh Bayati (Shahid Sadoughi University of Medical Sciences, 2024)
Background: Despite the extensive use of the gonadotropin-releasing hormone (GnRH) antagonist protocol in treating infertile women, particularly those with polycystic ovary syndrome (PCOS), there have not been sufficient evidence to compare the flexible and fixed variants in in vitro fertilization (IVF) cycles. Objective: This study aims to assess the treatment outcomes of flexible and fixed types of GnRH-antagonist protocol for IVF in women with PCOS. Materials and Methods: In this randomized clinical trial, 150 infertile women with PCOS, who were candidates for IVF, and referred to the Yazd Research and Clinical Center for Infertility, Yazd, Iran between October 2023 and February 2024 were included. Participants were divided into 2 groups (n = 75/each) based on the type of antagonist protocol (fixed or flexible). GnRH antagonist administration started on the 5 th day of gonadotropin treatment in the fixed group. In the flexible group when there was at least one follicle 12-14 mm, GnRH antagonist was started. Finally, the number of metaphase II oocyte, the quality of embryos, the duration of the stimulation cycle, the dose of gonadotropin, the number of GnRH-antagonist, and the rate of ovarian hyperstimulation syndrome were evaluated. Results: No statistically significant difference was observed in terms of cycle length and the total dose of gonadotropin between groups. Nevertheless, a notable distinction was observed in the total number of oocytes (17.84 vs. 15.5, p = 0.023) and mature oocytes (13.64 vs. 11.83, p = 0.019) in the flexible group compared to the fixed group. Conclusion: In conclusion, the IVF outcomes are more favorable in women with PCOS undergoing the flexible GnRH-antagonist protocol compared to the fixed protocol.